1965
DOI: 10.1111/j.1365-2621.1965.tb01882.x
|View full text |Cite
|
Sign up to set email alerts
|

Release of Cellular Constituents During Heat Inactivation of Endospores of Aerobic Bacilli

Abstract: SUMMARY Release of dipicolinic acid from spores of some species of Bacillus during heating at 100°C was determined. The total amount and rate of release of dipicolinic acid from these spores varied between species and strains, the most resistant spores releasing the least. Studies were made on Bacillus polymyxa and B. megaterium to determine the influence of buffers and pH on the liberation of dipicolinic acid, carbohydrate, and nitrogen. Release of these materials was usually least at pH 7.0 and greatest unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

1969
1969
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
(19 reference statements)
2
8
0
Order By: Relevance
“…These results are in complete agreement with the data obtained from the experiment on the effect of pH. Most heat-resistant spores release the least DPA under equal conditions (Walker et al, 1965). Spores of the rough variant were found more heat resistant (Rotman, 1967).…”
Section: Effect Of Heating Timesupporting
confidence: 91%
See 1 more Smart Citation
“…These results are in complete agreement with the data obtained from the experiment on the effect of pH. Most heat-resistant spores release the least DPA under equal conditions (Walker et al, 1965). Spores of the rough variant were found more heat resistant (Rotman, 1967).…”
Section: Effect Of Heating Timesupporting
confidence: 91%
“…1). Walker et al (1965) reported that endospores of aerobic bacilli release the least DPA at pH 7.0, with more acid being released under unfavorable conditions. Similar results were observed in this study.…”
Section: Effect Of Phmentioning
confidence: 99%
“…Third, DPA is released during wet-heat-induced spore inactivation, which is the focus of this study. The relationship between the release of DPA and the heat resistance of spores has been studied for spores from a number of Bacillus species, all showing that DPA release is slower than the loss of viability of the spores during heating (13,47). Although the correlation between DPA release and the spore death rate was complex, in these studies higher rates of death were associated with higher rates of DPA release.…”
mentioning
confidence: 92%
“…The same conclusion was reached in all these studies: that release of Dpa proceeds at a slower rate than loss of viability of spores during heating, suggesting that death precedes the release of Dpa. Walker & Matches (1965) suggested that the release of Dpa is a secondary reaction reflecting a change in cellular organisation which was primarily responsible for the inactivation of the spore.…”
mentioning
confidence: 99%